Textile EF shaped antenna based on reinforced epoxy for breast cancer detection by composite materials. (2021) - Sakthisudhan, K.; Murugesan, Bharani; Saravanan, V.; Sailaja, P.N.S.
Abstract: The EF shaped microstrip patch antenna has been fabricated by reinforced epoxy materials and printed on textile woven for breast cancer detection application is proposed in this research. The proposed wearable antennas have been examined with composite materials for coverage of cancer in cancerous organ, which results have been implemented for Microwave Imaging System. These proposed microstrip slots have been printed on the cotton and polyester woven materials by hand block printing technology. They have been offered the resonant at 3.32 GHz and 3.33 GHz respectively, which measured by Agilent (N99917A) Microwave Analyzer. These proposed results have been achieved 99.9% accuracy with fabricated prototypes. Since, these wearable modules have not reflected any kind of losses, which mounted on woven materials. Therefore, the proposed module has a low profile, wideband structure and also provide the wideband of coverage in terms of 27.7% and 26.13% respectively. Therefore, these proposed woven antennas have been examined with their measurement analysis.